Credit procedure of Mercantile Bank Limited: a case study of Mohakhali Branch - Pritha, Ishrat Jahan (BRAC University, 2014)
This internship report is submitted in a partial fulfillment of the requirements for the degree of Bachelor of Business Administration,2014.